From the mist - Thorpe, Kiki; Christy, Jana (New York : Random House, 2013)
Mysterious mist horses have come to Pixie Hollow. Kate befriends one, but Silvermist finds an old legend that says they might be dangerous.
2.5.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Horses -- Juvenile fiction; Fog -- Juvenile fiction; Fairies -- Fiction; Magic -- Fiction; Horses -- Fiction; Fog -- Fiction